EVALUATION OF THE WOUND HEALING POTENTIAL OF OINTMENT PREPARATION OF ETHYL-ACETATE EXTRACT OF MORINGA OLEIFERA (LAM) IN RATS - Coker, Morenike; Adejo, Grace; Emikpe, Benjamin; Oyebanji, Victor (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: This study examined the in vitro antibacterial property of extracts of Moringa oleifera and the effect of different concentrations of the ethyl-acetate extract on cutaneous wound using an ointment delivery base. The aim of the study was to screen the extracts with best antibacterial property and evaluate effectiveness of different concentrations of the best extract when delivery is modified to ensure prolonged contact and reduced frequency of administration using an ointment base delivery vehicle.Materials and Methods: Dried and pulverized leaves of Moringa oleifera were screened for secondary metabolites. Successive gradient extraction was carried out using n-hexane, ethyl acetate and methanol. Leaf extracts were screened against clinical wound isolates of Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae and Proteus mirabilis using agar cup diffusion technique. The ethyl acetate extract was investigated for its healing efficiency on excision wound model in rats. The study made use of wistar rats (150-180 kg), randomized into Gentamicin, M. oleifera ointment (5% and 3.25%), and ointment base treatment groups. Treatments were applied topically on days 0, 7 and 14. The percentage wound closure rate was measured and histopathology of the healed wounds carried out.Results: In vitro antimicrobial screening showed that ethyl-acetate extract was effective against the test isolates. Topical application of ointment with 3.25% of the plant extract resulted in faster wound closure rate, rapid epithelization, resolution of granulation tissue, and remodeling at histology.Conclusion: This may be due to less interference by components of M. oleifera which appear to retard wound healing at higher concentrations. Therefore, M. oleifera 3.25% ointment preparation is recommended topically for wound healing.